Persistent but dysfunctional mucosal SARS-CoV-2-specific IgA and low lung IL-1β associate with COVID-19 fatal outcome: A cross-sectional analysis - Ruiz, Maria Julia; Siracusano, Gabriel; Cottignies-Calamarte, Andréa; Tudor, Daniela; Real, Fernando; Zhu, Aiwei; Pastori, Claudia; Capron, Claude; Rosenberg, Arielle R.; Temperton, Nigel; Cantoni, Diego; Liao, Hanqing; et al. (Frontiers in Immunology, 2022)
The role of the mucosal pulmonary antibody response in COVID-19 outcome remains unclear. Here, we found that in broncho-alveolar lavages (BAL) from 48 patients with severe COVID-19 infected with the ancestral Wuhan virus, mucosal S1-, RBD-, S2-, and NP-specific IgA and IgG emerged in BAL-containing viruses early in infection and persist after virus elimination, with more IgA than IgG for all antigens tested. Furthermore, spike-IgA and spike-IgG immune complexes were detected in BAL, especially when lung virus has been cleared. BAL IgG and IgA recognized the four main RBD variants. BAL neutralizing titers were higher during viremic COVID-19 than later in infection. Patient with fatal COVID-19, in contrast to Survivors, developed higher levels of mucosal spike-specific IgA than IgG but lose neutralizing activities over time and had reduced IL-1beta in the lung. Altogether, mucosal spike and NP-specific IgG and S1-specific IgA persisting after lung SARS-CoV-2 clearance, and low pulmonary IL-1b correlate with COVID-19 fatal outcome. Thus, mucosal SARS-CoV-2-specific antibodies may have adverse functions beside protective neutralization.